Persistent DNA damage associated with ATM kinase deficiency promotes microglial dysfunction. Issue 5 (25th February 2022) - Bourseguin, Julie; Cheng, Wen; Talbot, Emily; Hardy, Liana; Lai, Jenny; Jeffries, Ailsa M; Lodato, Michael A; Lee, Eunjung Alice; Khoronenkova, Svetlana V
Abstract: The autosomal recessive genome instability disorder Ataxia–telangiectasia, caused by mutations in ATM kinase, is characterized by the progressive loss of cerebellar neurons. We find that DNA damage associated with ATM loss results in dysfunctional behaviour of human microglia, immune cells of the central nervous system. Microglial dysfunction is mediated by the pro-inflammatory RELB/p52 non-canonical NF-κB transcriptional pathway and leads to excessive phagocytic clearance of neuronal material. Activation of the RELB/p52 pathway in ATM-deficient microglia is driven by persistent DNA damage and is dependent on the NIK kinase. Activation of non-canonical NF-κB signalling is also observed in cerebellar microglia of individuals with Ataxia–telangiectasia. These results provide insights into the underlying mechanisms of aberrant microglial behaviour in ATM deficiency, potentially contributing to neurodegeneration in Ataxia–telangiectasia.